2017
DOI: 10.4218/etrij.17.0116.0385
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-Mode DynamicRonMeasurement of Large-Scale High-Power AlGaN/GaN HFET

Abstract: We propose pulse‐mode dynamic Ron measurement as a method for analyzing the effect of stress on large‐scale high‐power AlGaN/GaN HFETs. The measurements were carried out under the soft‐switching condition (zero‐voltage switching) and aimed to minimize the self‐heating problem that exists with the conventional hard‐switching measurement. The dynamic Ron of the fabricated AlGaN/GaN MIS‐HFETs was measured under different stabilization time conditions. To do so, the drain‐gate bias is set to zero after applying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…We used gallium nitride (GaN) FETs as the power switches. The fast switching speed, and low switching and conduction losses of a GaN‐based power semiconductor enable small‐size, highly efficient power conversion systems to be implemented . Several research groups have reported highly efficient and small‐size power conversion systems such as buck converters, boost converters, and inverters using GaN switching power devices .…”
Section: Proposed Ltcc‐based Synchronous Buck Convertermentioning
confidence: 99%
“…We used gallium nitride (GaN) FETs as the power switches. The fast switching speed, and low switching and conduction losses of a GaN‐based power semiconductor enable small‐size, highly efficient power conversion systems to be implemented . Several research groups have reported highly efficient and small‐size power conversion systems such as buck converters, boost converters, and inverters using GaN switching power devices .…”
Section: Proposed Ltcc‐based Synchronous Buck Convertermentioning
confidence: 99%
“…Thus, Faulty turn-on may be occurred as a result, which creates a serious problem. Therefore, the study to address this issue was accomplished [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%